Languages and compilers for parallel computing : 29th International Workshop, LCPC 2016, Rochester, NY, USA, September 28-30, 2016, Revised papers /: 29th International Workshop, LCPC 2016, Rochester, NY, USA, September 28-30, 2016, Revised papers. (2017) - Unknown
No abstract available